2008
DOI: 10.1590/s1413-73722008000200016
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de bebês prematuros relacionado a variáveis neonatais e maternas

Abstract: RESUMO.O estudo verificou a relação entre ansiedade materna, características neonatais e indicadores de desenvolvimento de crianças nascidas pré-termo aos 12 meses de idade cronológica corrigida. Foram avaliadas 14 crianças com as Escalas Bayley-II e suas mães com o Inventário de Ansiedade Traço-Estado. Os itens relativos à resolução de problemas, permanência do objeto, intencionalidade, linguagem e motricidade correlacionaram-se significativamente com variáveis neonatais do bebê e ansiedade materna. A maior g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
36

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 27 publications
1
15
0
36
Order By: Relevance
“…Prematurity was the only biological risk factor emphasized in this study in order to homogenize the sample since it has relevant effect in child development and is directly correlated with other risk factors such as low birth weight (27,28), the presence of associated diseases (2,28), the length of hospital stay after birth (27,28) and the need to stay on mechanical ventilation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity was the only biological risk factor emphasized in this study in order to homogenize the sample since it has relevant effect in child development and is directly correlated with other risk factors such as low birth weight (27,28), the presence of associated diseases (2,28), the length of hospital stay after birth (27,28) and the need to stay on mechanical ventilation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies 28,29 that assessed the motor development of infants from adolescent and adult mothers showed that a lower maternal age can be considered a risk factor for the motor impairment in children. We must highlight that different factors interact, such as task demands and environmental conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Segundo Carvalho (2005), a presença de sintomas de ansiedade e depressão pode significar situação de risco para a relação mãe-bebê, comprometendo a qualidade dos cuidados maternos. Fraga et al (2008) também encontraram evidências sobre as repercussões emocionais negativas nas crianças, em função dos quadros de ansiedade materna.…”
Section: Resultsunclassified
“…Segundo Padovani et al (2004), mães que acompanham os filhos internados costumam apresentar altos níveis de ansiedade e depressão, desencadeando sentimentos de apoio emocional inadequado ao bebê. Outros estudos têm indicado que a ansiedade materna traz prejuízos ao desenvolvimento emocional da criança (Linhares, Carvalho, Machado, & Martinez, 2003;Fraga et al, 2008;Correia & Linhares, 2007).…”
unclassified